PENINGKATAN KETERAMPILAN MELALUI PEMBUATAN ECO-ENZYM SEBAGAI UPAYA PENGEMBANGAN USAHA KEWIRAUSAHAAN KELOMPOK WANITA TANI BUNDA ATIRAH - Elza Safitri; Yosmed Hidayat; Zikra Zikra; Abizar Abizar; Revani Assya Aulia Putri; Eunike Deska Bali (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
BUNDA ATIRAH Farming Women's Group Some of the members are housewives with low education and are classified as economically weak. The activities carried out by KWT aim to improve members' skills which can increase family income. The activity that has been underway is cultivating secondary crops. The palalawi harvest has been marketed to members and communities around the KWT location. Even though KWT has produced agricultural products in the form of cassava leaves, kale, spinach, etc., the results obtained have not been able to improve the family's economy significantly. For this reason, it is necessary to try other activities that can increase the family income of KWT members. One of the businesses planned to be carried out is an agricultural business. The planned business development into the agricultural sector is the manufacture of eco-enzymes. Making eco-enzymes can be done with not too much capital because it only uses organic household waste. For this reason, the service team provides KWT guidance in making eco-enzymes. This is in accordance with KWT Bunda Atirah's needs in developing business innovation towards agriculture. This activity was carried out for 4 months starting from preparing the materials, making eco-enzymes for 2 months and applying them to cultivated plants (hydroponics).Keywords: eco-enzym; Entrepreneurship Development; Farmers